Three Stages and Main Provisions of Institutionalization of International Forums in Solving Global Economic Problems (1997–2020) - Maria I. Kiseleva (Управленческое консультирование)
This article examines the institutional development of a forum, taking SPIEF and the Roscongress Foundation as a case study. The organization and event can be loosely divided into three periods: parliamentary (1997–2005), governmental (2006–2015), and presidential (2016 — present day). The article sets forth the minimum criteria of the work involved. The three periods are analysed, along with the need for each transition, and the organizational process involved for each one. Factors underpinning the stability of the system as a whole also come under examination.